Σ‐Aromaticity in an Unsaturated Ring: Osmapentalene Derivatives Containing a Metallacyclopropene Unit1. (4th February 2015) - Zhu, Congqing; Zhou, Xiaoxi; Xing, Hongjie; An, Ke; Zhu, Jun; Xia, Haiping
Abstract In general, aromaticity can be clarified as π‐ and σ‐aromaticity according to the type of electrons with major contributions. The traditional π‐aromaticity generally describes the π‐conjugation in fully unsaturated rings whereas σ‐aromaticity may stabilize fully saturated rings with delocalization caused by σ‐electron conjugation. Reported herein is an example of σ‐aromaticity in an unsaturated three‐membered ring (3 MR), which is supported by experimental observations and theoretical calculations. Specifically, when the 3 MR in cyclopropaosmapentalene is cleaved by ethane through two isodesmic reactions, both of them are highly endothermic (+29.7 and +35.0 kcal mol−1). These positive values are in sharp contrast to the expected exothermicity, thus indicating aromaticity in the 3 MR. Further nucleus‐independent chemical shift and anisotropy of the current‐induced density calculations reveal the nature of σ‐aromaticity in the unsaturated 3 MR.